Treatment of Posttubercular Syringomyelia Not Responsive to Antitubercular Therapy: Case Report and Review of Literature - Giuseppe Canova; Alessandro Boaro; Enrico Giordan; Pierluigi Longatti (Journal of Neurological Surgery Reports, 2017)
Posttubercular adhesive arachnoiditis is a rare, late complication of tubercular meningitis. Syringomyelia can develop as a consequence of intramedullary cystic lesions and cerebrospinal fluid (CSF) flow disturbance around the spinal cord, even after successful chemotherapy. We reviewed the literature related to posttubercular syringomyelia treatment and suggest a new combined surgical approach. A 25-year-old Nigerian male patient presented with legs numbness, urinary disturbance, and legs weakness. Spinal magnetic resonance revealed a T5-T7 syringomyelia, secondary to adhesive spinal arachnoiditis related to a history of tuberculous meningitis. Adhesiolysis by direct visualization with a flexible endoscope was performed and a handmade S-italic syringe-subdural shunt was placed to restore CSF flow. During the postoperative course, the neurological deficits improved together with the resolution of the syrinx. Long-term magnetic resonance imaging follow-up documented no recurrences or shunt displacements. We suggest that, when antitubercular therapy is not effective to resolve postarachnoiditis syrinx, arachnolysis with a flexible endoscope together with the placement of an S-italic shunt allowed free CSF communication between the syrinx and the subarachnoid space. Furthermore, we support that the use of an s-shaped shunt could prevent displacement or migration of the device and allows an easier revision in case of acute or late complications.